Regulation of semen quality by fatty acids in diets, extender, and semen - Yuan, Chongshan; Wang, Jun; Lu, Wenfa (Frontiers in Veterinary Science, 2023)
Fatty acids (FAs) are classified into different types according to the degree of hydrocarbon chain saturation, including saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), omega-3 polyunsaturated fatty acids (omega-3 PUFAs) and omega-6 polyunsaturated fatty acids (omega-6 PUFAs), which play an important role in maintaining semen quality. This review focuses on the regulation of FAs in semen, diet and extender on semen quality, and expounds its effects on sperm motility, plasma membrane integrity, DNA integrity, hormone content, and antioxidant capacity. It can be concluded that there are species differences in the FAs profile and requirements in sperm, and their ability to regulate semen quality is also affected by the addition methods or dosages. Future research directions should focus on analyzing the FAs profiles of different species or different periods of the same species and exploring suitable addition methods, doses and mechanism of regulating semen quality.